Serum mannose-binding lectin levels are decreased in Behçet's disease and associated with disease severity - (:unkn) unknown (My University, 2005)
Objective. To investigate serum levels of mannose-binding lectin (MBL), a complement-like protein of collectin family, in patients with Behçet's disease (BD). Methods. MBL levels were measured in sera of 130 patients with BD, 64 patients with recurrent oral ulcerations (ROU), and 105 healthy controls (HC) with ELISA. Results. Patients with BD had significantly lower median serum MBL levels compared to HC (1857 vs 3136 ng/ml, p = 0.001). No significant difference was observed in median serum MBL levels between BD and ROU (2309 ng/ml, p = 0.252). Low MBL levels (≤ 500 ng/ml) were present in a higher proportion of BD patients compared to HC (29% vs 16%, p = 0.021). A severe disease course (total clinical severity score ≥ 4) was more frequently observed in BD patients with very low serum MBL levels (≤ 100 ng/ml) (19% vs 6%, p = 0.046). When serum MBL levels were analyzed separately according to gender, the frequency of vascular disease was higher in men with very low serum MBL levels (80% vs 42%, p = 0.042). Conclusions. MBL deficiency might contribute to the pathogenesis of BD and affect its clinical course.
Keywords: Behçet's disease; Mannose-binding lectin; Total clinical severity score